2000
DOI: 10.1109/36.842001
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of forest parameters using CARABAS-II VHF SAR data

Abstract: Abstract-The use of airborne CARABAS-II VHF (20-90MHz) SAR data for retrieval of forest parameters has been investigated. The investigation was performed at a test site located in the southwest of Sweden consisting mainly of Norway spruce forests. Regression models predicting forest parameters from radar backscattering amplitude were developed and evaluated. The results showed a linear relationship between backscattering amplitude and forest stem volume, stem diameter, and tree height. The analysis also showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 14 publications
2
49
0
Order By: Relevance
“…SAR applies longer wavelength microwave energy, which has stronger penetration than the visible and near infrared bands used by ALS systems and avoids interference caused by cloud cover [46]. SAR data with appropriate wavelengths can detect tree trunks due to strong canopy penetration and the backscatter has a linear relationship with stocking volume even for dense forests [47,48]. The ability of SAR to penetrate the canopy and detect trunks allows lower spatial resolution to meet the requirements for mapping individual trees compared to that required by ALS or multispectral sensors [45].…”
Section: Active Data Sources For Itcdmentioning
confidence: 99%
“…SAR applies longer wavelength microwave energy, which has stronger penetration than the visible and near infrared bands used by ALS systems and avoids interference caused by cloud cover [46]. SAR data with appropriate wavelengths can detect tree trunks due to strong canopy penetration and the backscatter has a linear relationship with stocking volume even for dense forests [47,48]. The ability of SAR to penetrate the canopy and detect trunks allows lower spatial resolution to meet the requirements for mapping individual trees compared to that required by ALS or multispectral sensors [45].…”
Section: Active Data Sources For Itcdmentioning
confidence: 99%
“…Studies using CARABAS, a radar sensor similar to BioSAR, have shown that the VHF backscatter mechanisms are mainly dominated by ground-trunk doublebounce scattering mechanisms for simple forest structures such as gently sloped coniferous forests (Fransson et al 2000;Hallberg et al 2005). The longer wavelength radar has good foliage penetration; hence, the foliage-floor and trunk-foliage double-bounce scattering can be considered negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing SAR data have found that the sensitivity of the radar backscatter coefficient to biomass disappears in forests with biomass exceeding 100 tonnes/ha (Dobson et al 1992;Fransson et al 2000;Imhoff et al 2000;Imhoff 1995). The usual 1-to 10-GHz frequencies are often intercepted by the crown layer of the canopy in dense forests, and twigs, needles, and smaller branches in the top layers of the canopy are the major scatterers at these wavelengths (Fransson et al 2000). Using lower frequencies, e.g., the Pband (around 440 MHz), the sensitivity to biomass increases, but saturation still occurs at 100-200 tonnes/ha biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing developments in active remote-sensing methods-so called because they involve the transmission of signal and measurement of the return signal-offer a promising source of additional information about the landscapes that animals inhabit. For example, light detection and ranging (lidar), can provide measurements of forest canopy height and vertical canopy structure (Dubayah and Drake 2000;Hyde et al 2006), and radio detection and ranging (radar) can provide measurements of aboveground biomass and basal area, and measurements of moisture levels in the canopy and in the soil (Fransson et al 2000;Quiñones and Hoekman 2004;Saatchi et al 2007;Treuhaft et al 2003;Treuhaft and Siqueira 2000). Another significant development is the increasing availability of remotely sensed imaging spectrometry, which yields a continuous reflectance spectrum for each pixel rather than reflectance values in a few specific wavelengths.…”
Section: Future Directionsmentioning
confidence: 99%